ANALYSIS ON STUDENTS’ ENGLISH-INDONESIAN TRANSLATION METHOD OF DESCRIPTIVE TEXT - Charitas Dei Lisepung (Yayasan Seri Amal Medan, 2022)
This thesis is a study about analysis on student’s English-Indonesia translation method of descriptive text. The objective of this study is to find the translation method that used by the students in translating descriptive text and to identify the most dominant translation method that used by the students in translating descriptive text. The subject of this study is the second semester students of English Department in HKBP Nommensen University. The data was a translation test. The study uses descriptive qualitative method as a research design. Finally, the result of this study shows there are 6 types of translation method that used by the students in translating the text, they are word-for-word translation (1,95 %), literal translation (22,27%), faithful translation (22,66%), free translation (32,03%), communicative translation (10,93%), semantic translation (10,16%), since the other method are rarely to use for translating text especially descriptive text. And the most dominant translation method that used by the students is free translation (32,03%). Based on the result of this study, the writer only find 6 translation method from 8 types that should be based on Peter Newmark’s translation method theory. The students were difficult to translating the text and some just showing what are in their mind. The writer suggest that the teacher keep their attention in teaching the students about translation and improving students vocabulary so that they can use the good English to Indonesia as well in translating text by using translation method.